Research evolution of flat peach (Prunus persica (L.) Batsch): a decadal bibliometric analysis - Gedamu, Abebe Misganaw; Li, Yong; Wu, Jinlong; Cao, Ke; Anees, Muhammad; Wang, Zhaohui; Liu, Suning; Xing, Hongyang; Wei, Pengcheng; Jehangir, Muhammad; Hayat, Umar; Ren, Wei; et al. (Frontiers in Plant Science, 2025)
IntroductionThe flat peach (Prunus persica (L.) Batsch.), characterized by its oblate shape and determined by a known genetic inversion, is a high-value cultivar gaining global market share. Mapping the intellectual landscape of its research is crucial to consolidate knowledge and direct future scientific and breeding programs.MethodsA comprehensive bibliometric analysis was conducted on a curated dataset of forty open-access research articles published between 2010 and 2024, sourced from Web of Science and Scopus. Following rigorous data deduplication, the bibliometrix R package was employed to analyze publication trends, collaboration networks, and keyword co-occurrence patterns. Collaboration networks were subsequently visualized and analyzed using VOSviewer.ResultsThe analysis identified a striking surge in annual publications, particularly post-2019, underscoring growing interest. China was the unequivocal dominant force in production and citation impact. Key research themes clustered around “fruit quality,” “genetics,” and “postharvest physiology,” with “quality” exhibiting the strongest network centrality. The network analysis identified “flat peach” as a central hub, demonstrating the highest co-occurrence link strength and affirming its strong, multifaceted connections within the research domain.DiscussionThis first systematic bibliometric review delineates the rapid evolution of flat peach research, highlighting its core drivers and conceptual focus. The steep growth in output reflects rising academic and commercial interest. Critically, the analysis identifies significant gaps in molecular genomics, postharvest optimization, and climate resilience research. These findings provide a strategic, evidence-based roadmap to align future research priorities with market demands and sustainable cultivation challenges.